Facility Layout Dalam Upaya Optimalisasi dan Keberlanjutan Laboratorium Untuk Mendukung Teaching Factory: Facility Layout in Efforts to Optimize and Sustainability of Laboratories to Support Teaching Factory - Yesica Novrita Devi (Program Studi Teknologi Informasi, 2019)
Good facility layout planning will increase the effectiveness and efficiency of resource so that it affects the total performance of a system that implements the process in it. The process occurring in a system needs to be supported by human behavior to support the sustainability. The purpose of this study was to provide a facility layout design for the management planning stage of the Maritime Business Development Laboratory and the implementation of 5R concept to optimize the laboratory management of Surabaya State Shipbuilding Polytechnic. The method used in this research was descriptive qualitative by designing facility layout using the ARC method and explaining the implementation of 5R as a culture to support a sustainable working system. The results of the study were outlined in the form of facility layout design according to the Activity Relationship Chart (ARC) and the stages carried out by the laboratory in the application of the 5R as the working culture principles